Diversified marriage system on the Tibetan plateau: decline, revival and variation in the perspective of legal anthropology - Wang, Tianyu (2024)
This article explores the social and cultural dynamics reflected by the decline, revival and variation of the diversified marriage system, considering the context of changes in the social legal environment and social structure of the Qinghai Tibet Plateau, with polygamy as a typical example. The research focuses on the women’s role in it and anticipates the future development of polygamy on the Qinghai Tibet Plateau. The investigation and application of this paper are a re-interpretation of prior studies on gender power and women's position. From a cross-cultural standpoint, the prevalence and persistence of polyandry refutes the mechanical interpretation of women's universal subservient role. The emphasis on women's roles and position in polyandry families seeks to confirm the complexities of gender power and women's standing in society. Both theoretical concept invention and research path exploration are targeted at moving further into the investigation of similar challenges. The focus and exploration of the female group in polyandry in this article have supplemented prior studies on the women’s status and identified difficulties that need to be addressed.